Anxiety Sensitivity and Smoking Behavior Among Trauma-Exposed Daily Smokers: The Explanatory Role of Smoking-Related Avoidance and Inflexibility. (January 2016) - Bakhshaie, Jafar; Zvolensky, Michael J.; Salazar, Adriana; Vujanovic, Anka A.; Schmidt, Norman B.
Anxiety sensitivity (AS), defined as the extent to which individuals believe that anxiety-related sensations have harmful consequences, is associated with smoking processes and poorer clinical outcomes among trauma-exposed smokers. Yet the specific mechanisms underlying this association are unclear. Smoking-specific avoidance and inflexibility is a construct implicated in multiple manifestations of mood regulation that may underlie smoking behavior. The current study examined the explanatory role of smoking-specific avoidance and inflexibility in terms of the relation between AS and indices of smoking behavior among trauma-exposed smokers. The sample consisted of 217 treatment-seeking adult smokers (44% female; M age = 37.8; SD = 13.2; age range: 18-65 years), who were exposed to at least one lifetime Criterion A trauma event ( Diagnostic and Statistical Manual of Mental Disorders [4th ed., text rev.; DSM-IV-TR ] Criterion A for trauma exposure). Bootstrap analysis (5, 000 re-samples) revealed that AS was indirectly related to the (a) number of cigarettes smoked per day, (b) number of years being a daily smoker, (c) number of failed quit attempts, and (d) heaviness of smoking index among trauma-exposed smokers through its relation with smoking-specific avoidance and inflexibility. These findings provide initial evidence suggesting that smoking-specific avoidance and inflexibility may be an important construct in better understanding AS–smoking relations among trauma-exposed smokers. Future work is needed to explore the extent to which smoking-specific avoidance and inflexibility account for relations between AS and other smoking processes (e.g., withdrawal, cessation outcome) in the context of trauma and smoking comorbidity.